Enzimas que hidrolisam nucleotídeos de adenina em sinaptossomas de córtex cerebral e plaquetas de ratos desmielinizados pelo brometo de etídio e tratados com interferon-β - Spanevello, Roselia Maria (2006)
The activities of the enzymes NTPDase (E.C. 3.6.1.5, apyrase, CD39) and 5 -nucleotidase (E.C. 3.1.3.5, CD73) were analyzed in synaptosomes from the cerebral cortex and platelets of rats submitted to demyelination by ethidium bromide (EB) associated with interferon-β (IFN-β) treatment. The following groups were studied: I - control (saline), II - (saline and IFN-β), III - (EB) and IV - (EB and IFN-β). After 7, 15 and 30 days of the surgical procedure, the animals (n=5) were sacrificed and samples was collected for enzymatic assays. The results showed that NTPDase and 5 -nucleotidase activities was increased in synaptosomes of the group III after 7 and 15 days in relation in the control group. The treatment with IFN-β increased the ATP hydrolysis in the groups II e IV after seven days and in the group IV in fifteen days, whereas no alteration was observed in ADP hydrolysis in relation the group I. The 5 -nucleotidase activity in synaptosomes also increased in the group II e IV in fifteen days, when compared with the control group. In relation the ectonucleotidases in platelets, the results demonstrated that the NTPDase activity was reduced in the group III after seven and fifteen days and the IFN-β treatment increased nucleotides hydrolysis in the group IV with relation the group III. In the group II was observed a reduction in the ATP and ADP hydrolysis after 7 days and an increase after 15 days with relation the group I. The 5 -nucleotidase activity in platelets increased in the group IV after 7days and reduced in the groups III and IV after 15 days when compared with the control. In 30 days, no significant alteration was observed in the enzymes activities in synaptosomes and platelets of the groups studied. These results demonstrated that the NTPDase and 5 -nucleotidase activities are altered in synaptosomes and platelets the rats after an event the toxic demyelination in the central nervous system and that IFN-β interfered with the adenine nucleotide hydrolysis.